Definite influence of the extraction methods on the chemical composition of virgin olive oil - Aparicio, R.; Sánchez Navarro, M.; Ferreiro, M. S. (Grasas y Aceites, 1991)
The extraction methods of virgin olive oil affect the quantification values of some chemical compounds. Statistical tests and procedures have been applied to a set of 142 samples collected from all over Andalusia and characterized by 55 chemical compounds. It has been estimated that two aliphatic alcohols, one sterol and one fatty acid have the best significance levels identifying the extraction methodology (pressure, centrifugation). Stepwise Lineal Discriminant procedure has been used to characterize olive oils by the extraction systems. 205 samples from other provinces, varieties or harvests were used to verify these decision equations.